The relationship between parental involvement and psychological adjustment among Chinese children with autism spectrum disorder in the transition from kindergarten to primary school: A chain-mediating model - Hou, Yujia; Yan, Tingrui; Zhang, Junfang (Frontiers in Psychology, 2023)
This study examined the impact of parental involvement on the psychological adjustment of children with autism spectrum disorder (ASD), and the role of parenting self-efficacy and parenting stress in the transition from kindergarten to primary school. Using the questionnaires, we collected data from 237 Chinese parents of children with ASD. Mediation analyses showed that parental involvement partially promoted the psychological adjustment of children with ASD, which was reflected in the fact that parental involvement promoted children's prosocial behavior but did not reduce their emotional/behavioral problems. Mediation analyses also revealed the role of the mediator in parenting stress between parental involvement and the psychological adjustment of children. Additionally, the results suggested that parenting self-efficacy and parenting stress played a chain-mediating role in the association between parental involvement and psychological adjustment in children with ASD. These findings enhance our understanding of the mechanisms underlying the relationship between parental involvement and psychological adjustment in children with ASD in the transition from kindergarten to primary school.